Racial Discrimination in John Neufeld's Edgar Allan - Mas Muhammad Idris (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2017)
Racial Discrimination of colored people has become popular in the history of the United Stated. The white people used to do this towards the black people. They got inconveniently treatments because they were black; furthermore they also suffered inequitable of privilege. However, it happens not only in the real life but also lies in the story of Edgar Allan novel. Therefore this research aimed at analyzing the racial discrimination which lies on the Edgar Allan novel written by John Neufeld, American Novelist for young adults and adults. In his first novel, Edgar Allan, the researcher found sorts of structural racism occurred in term of utterances and dialogs amongst the people in the novel. Related to the issue of racial discrimination which occurred in Edgar Allan novel, Lawrence and Kelleher (as cited in Nursani’s thesis, 2013) defined the term of structural racism as a system of hierarchy and inequity, primarily characterized by white supremacy to maintain their authority over oppressed people. In addition, the structural racism also occurs in this novel, such as in the form of aversive racial attitudes, individual racism, institutional racism, and interpersonal racism. Besides, it is also supported by many expressions of prejudice for examples, antilocution of prejudice, avoidance of prejudice, discrimination of prejudice and extermination of prejudice. So, to interpret the condition above, this research utilized descriptive qualitative approach to depict how the white people execute the subordinate people through their treatments of racism. For this case, Edgar Allan was the one who suffered all these treatments as he was really black taken from the adoption of agency by this white family. He was still three years old. Hence, he could not against this racial discrimination till he had to be returned to the adoption agency.